2019
DOI: 10.1029/2018jb016742
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Influence of Static and Dynamic Stress Perturbations On the Occurrence of a Shallow, Slow Slip Event in Eastern Taiwan

Abstract: We report the first evidence for the detection of a slow slip event in the Longitudinal Valley, in eastern Taiwan. The slow event, which lasted about 3.5 days, has been detected by borehole strainmeters. It occurred at shallow depths (about 2 to 4 km), either on the Longitudinal Valley Fault or on the Central Range Fault. Here we investigate whether the event occurrence was influenced by transient and periodic stress perturbations, in particular by the June 2013 Mw 6.2 Nantou earthquake, which occurred about 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…To conclude, while a SSE was detected at the transition between the creeping section of the LVF and the locked zone (Canitano et al., 2019), we now show that the fault can also host larger events at seismogenic depths. A limited fraction (about 15%–35%) of ∼0.15–0.35 m of the slip deficit accumulated in 2011 (Figure 4e) has been accommodated by the SSE, additional and/or recurrent aseismic transient slip should likely help to release the remaining slip deficit.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 66%
See 2 more Smart Citations
“…To conclude, while a SSE was detected at the transition between the creeping section of the LVF and the locked zone (Canitano et al., 2019), we now show that the fault can also host larger events at seismogenic depths. A limited fraction (about 15%–35%) of ∼0.15–0.35 m of the slip deficit accumulated in 2011 (Figure 4e) has been accommodated by the SSE, additional and/or recurrent aseismic transient slip should likely help to release the remaining slip deficit.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 66%
“…It rather suggests a triggering cascade of ruptures (e.g., Lengliné & Marsan, 2009), in which event 1, likely triggered by aseismic slip, has then ruptured close-by, but distinct, asperities (as events 2 and 3), together partially rupturing the main asperity (event 54). Overall, burst-type REs are likely caused by local, transient stress concentration from nearby earthquakes and/or aseismic slip events (Templeton et al, 2008) and they are also observed during postseismic slip on the LVF (Canitano et al, 2018a) To conclude, while a SSE was detected at the transition between the creeping section of the LVF and the locked zone (Canitano et al, 2019), we now show that the fault can also host larger events at seismogenic depths. A limited fraction (about 15%-35%) of ∼0.15-0.35 m of the slip deficit accumulated in 2011 (Figure 4e) has been accommodated by the SSE, additional and/or recurrent aseismic transient slip should likely help to release the remaining slip deficit.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 58%
See 1 more Smart Citation
“…There have been many reports of earthquake triggering (e.g., Hill et al 1993;Brodsky et al 2000;Kilb et al 2000;Miyazawa et al 2008;van der Elst and Brodsky 2010;Richards-Dinger et al 2010;Miyazawa 2011;Parsons and Velasco 2011;Lin 2012;Pollitz et al 2012;van der Elst et al 2013;Yukutake et al 2013;Johnson and Bürgmann 2016;Miyazawa 2016;Uchida et al 2016;Yoshida 2016). Besides the seismic event triggering, triggering of very low-frequency earthquakes, tremors, slow slip events (SSEs), and creep events has been observed (e.g., Allen et al 1972;Obara 2009;Itaba and Ando 2011;To et al 2015;Araki et al 2017;Miyazawa 2019;Canitano et al 2019;Katakami et al 2020). A likely mechanism behind earthquake triggering has been based on the rate-and state-dependent friction (RSF) law (Dieterich 1979;Ruina 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that distant earthquakes can trigger tectonic tremors (e.g., Chao et al, 2013; Miyazawa & Mori, 2005; Miyazawa & Brodsky, 2008; Peng & Gomberg, 2010; Rubinstein et al, 2007; Shelly et al, 2011) and VLFEs (e.g., Miyazawa, 2019; To et al, 2015). However, the dynamic triggering of both shallow and deep, detectable ( M w > 5.5) SSEs is relatively rare (Araki et al, 2017; Canitano et al, 2019; Itaba & Ando, 2011; Wallace et al, 2017; Zigone et al, 2012). Among them, Wallace et al (2017) reported the large‐scale dynamic triggering of shallow (<15‐km depth) SSEs in New Zealand during the passage of Kaikoura earthquake waves.…”
Section: Introductionmentioning
confidence: 99%